PENGARUH PENERAPAN PEER TEACHING TERHADAP TINGKAT KETERLIBATAN (STUDENT ENGAGEMENT), MOTIVASI, DAN HASIL BELAJAR PESERTA DIDIK KELAS X SMA GLOBAL PRESTASI PADA MATERI TRIGONOMETRI - Marlina, Reni; Hananto, Hananto (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The selection of learning strategies is very important, the right strategy will support the achievement of the desired learning objectives. This study aims to determine the effect of the application of peer teaching on student engagement, motivation, and learning outcomes of grade X students at Global High Prestasi School on Trigonometry material. This quantitative research with the quasi-experiment involves variables related to student engagement, motivation, and learning outcomes, while the independent variable is the application of peer teaching. There were 50 students in grade X who were the subjects of research and were divided into two groups that received different treatments: group 1 was an experimental class and group 2 was a control class, where each group consisted of 25 students. The collection of engagement and motivation instruments uses questio nnaires and observation sheets, while the learning outcomes are in the form of written tests (pretest and posttest). The instrument was tested using a Multivariate Analysis of variance (MANOVA) and an independent t-test with a significant level of 5% (α = 0.05). The results showed the influence of the application of peer teaching in both groups and the difference between the level of engagement, motivation, and learning outcomes of students shown in the t-test table in the sig column. (2-tailed) line Equal variances are assumed with significant values of the same variables of engagement and motivation of 0.000 and learning outcomes of 0.015, which means less than 0.05.